2018
DOI: 10.1039/c8cp00985f
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine substituent effect on the stereochemistry of catalyzed and non-catalyzed Diels–Alder reactions. The case of R-butenone with cyclopentadiene: a computational assessment of the mechanism

Abstract: The present work studies theoretically the mechanisms involved in the fluorine substituent effect on the stereochemistry of Diels-Alder reactions. The case of R-butenone with cyclopentadiene is used for the purpose of modelling more general α-fluoro-α,β-unsaturated carbonyl compounds, in catalyzed and uncatalyzed cases. A thorough analysis of the mechanism is performed using energy decomposition analysis (EDA) and conceptual DFT tools. It is shown that the endo conformation is privileged in all the studied cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…In a previous study, 56 it was determined that the dispersion energy plays an important role in Diels–Alder reactions selectivity. Thus, the dispersion energy incidence on these reactions kinetics is evaluated by comparing the relative energies of the four TS optimized with the ωB97XD functional (which explicitly includes some dispersion) with the ones optimized with MPWB1K.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, 56 it was determined that the dispersion energy plays an important role in Diels–Alder reactions selectivity. Thus, the dispersion energy incidence on these reactions kinetics is evaluated by comparing the relative energies of the four TS optimized with the ωB97XD functional (which explicitly includes some dispersion) with the ones optimized with MPWB1K.…”
Section: Resultsmentioning
confidence: 99%
“…To uncover the effect of solvent‐solute interactions along the reaction process, further calculations have also been performed considering tetrachloromethane as solvent. Indeed, several previous studies devoted to polar [4 + 2] reactions have indicated that the inclusion of solvent effects on geometry optimization produces only minor changes in comparison with that of gas‐phase 55,56 . The total energies of the first step in tetrachloromethaneare given in Table S9, whereas relative ones are given in red in Scheme 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It fast delivers energies computed from densities self‐consistently optimized with the PBE exchange‐correlation potential. As previously discussed by some of us, this alternative protocol may induce a performance deterioration more or less important depending on the number of empirical parameters. Energies reported here may thus differ somewhat from results reported in literature.…”
Section: Computational Detailsmentioning
confidence: 91%
“…The ASM 31 of reactivity is a powerful method contributing to the current understanding of chemical transformations. A wide range of S C H E M E 1 The Diels-Alder reaction between 2-bromocyclobutenone and 1,3-R-butadiene (Dn-1 to Dn-10) reactions and processes such as endo/exo stereoselectivity, 32 transition metal-mediated reactions, cycloaddition reactions and biological processes were studied. 13,[33][34][35][36][37][38][39][40][41][42][43] The ASM, 44 also called distortion/interaction model has been introduced by Houk et al 11,[44][45][46] This is a systematic extension of fragment approach from equilibrium structures to transition states including the nonstationary points lying along a reaction path.…”
Section: Activation Strain Modelmentioning
confidence: 99%